Development of force and temperature controlled friction stir welding machine (FSW) for dissimilar metal joining application - Ishak, M. (2018)
The first patent application of Friction Stir Welding (FSW) was filed in the United Kingdom in December 1991 which was invented by Wayne Thomas at TWI. The FSW process is currently patented by TWI in most industrial country and licensed for over 183 users. Friction stir welding and its variants friction stir spot welding and friction stir processing are used for the following industrial applications such as shipbuilding and offshore, aerospace, automotive, rolling stock for railways, general fabrication, robotics, and computers. Development of the process is underway in many companies, research institutes and universities throughout the world, and the activity level is growing. Applications have been reported in most industry sectors. In this report, design and fabrication of the FSW machine were exposed along with the results for the dissimilar metal welding.